The Effect of Income, Tax Literacy, Utilization of Tax Applications on MSME Taxpayer Compliance (Empirical Study on MSME Taxpayer Compliance Registered at KPP Pratama Pondok Aren) - Rosanti; Simorangkir, Rona Tumiur Mauli Carolin (Baca Dulu Publisher, 2024)
This study aims to determine and analyze the Effect of Income, Tax Literacy, Tax Application Utilization on MSME Taxpayer Compliance. This research may contribute to explaining the Theory of Planned Behavior and Technology Acceptance Model. This research contribution is intended for taxpayers, especially MSME actors in fulfilling their tax obligations. As well as being an evaluation material for the government, especially at the Directorate General of Taxes in providing regulations or providing convenience for taxpayers, with the aim of improving in order to achieve the desired tax revenue target. The object used in this study is MSME Taxpayers in the Pondok Aren Pratama Tax Service Office Area. This study used quantitative research methods and used causal research design. Data collection in this study used primary data sourced from the distribution of questionnaires distributed directly and also through google form to respondents consisting of MSME owners. The determination of the number of samples was carried out using the Slovin formula and obtained the results of 100 samples and the sampling method in this study used random sampling. The data analysis used in this study used SmartPLS Version 3.0 software. The results of this study show that the effect of income, tax literacy and the use of tax applications has a positive and significant impact on the compliance of MSME taxpayers KPP Pratama Pondok Aren.